2018
DOI: 10.1051/e3sconf/20183106008
|View full text |Cite
|
Sign up to set email alerts
|

The Presence Of Rat And House Sanitation Associated With Leptospira sp. Bacterial Infection In Rats (A Cross Sectional Study In Semarang, Central Java Province, Indonesia)

Abstract: The Gajah Mungkur sub-district in Semarang, Indonesia had highest leptospirosis cases (reported in human with seven infected and one dead) in 2015. The purpose of this study was to analyze the association between house sanitation and density of rats with Leptospira sp. infection in rats. The study design was cross sectional observational analytic. The number of 308 trapswere placed in study sites over three consecutive nights afterwards. Every houses were placed with four traps, inside and outside. Trapped rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Prevention of leptospira infection in humans can be done by reducing the rat population as pathogenic animals carrying leptospira bacteria. The reduction of the rat population is made by making permanent changes to the environment in which the mice breed [16]. Almost all research in this study found that there was a significant relationship between the incidence of leptospirosis with the presence of mice.…”
Section: Main Findingsmentioning
confidence: 67%
See 2 more Smart Citations
“…Prevention of leptospira infection in humans can be done by reducing the rat population as pathogenic animals carrying leptospira bacteria. The reduction of the rat population is made by making permanent changes to the environment in which the mice breed [16]. Almost all research in this study found that there was a significant relationship between the incidence of leptospirosis with the presence of mice.…”
Section: Main Findingsmentioning
confidence: 67%
“…This transmission often occurs because there is a pool of water and soil that has been contaminated by animal urine containing leptospira [14,15]. Meanwhile, indirect transmission occurs due to contact between the skin that is not wounded with water contaminated with mouse urine in a time long time [16].…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male rodents may exhibit aggressive behaviour. On the other hand, several previous studies reported that more female rodents were captured [27,28]. Female rodents are easier to catch because they enter and exit the nest frequently in search of food, whereas male rodents serve as nest guards [21].…”
Section: Discussionmentioning
confidence: 99%
“…Houses that have less lighting, ceilings that are not closed, and are without ventilation are perfect breeding grounds for rats. 17,21,22 Apart from the existence of rats as a reservoir and environmental conditions supporting their habitat, human behaviour can also increase the risk of infection with Leptospira bacteria. Not only behaviour in keeping the environment clean and not baiting rats to nest, the behaviour of wearing boots when it rains or floods, and washing feet after outside activities are behaviours that can reduce the risk of transmission of leptospirosis.…”
Section: Discussionmentioning
confidence: 99%